Review of the Australian leafhopper genus Trocnada with notes on related genera (Hemiptera: Cicadellidae: Iassinae) - Dai, Wu; Dietrich, Christopher H. (Zootaxa, 2012)
The Australian leafhopper genus Trocnada Walker is reviewed and includes three previously described species: T. alpinaEvans, T. dorsigera Walker and T. minuta Evans. Redescriptions of the genus and species are provided and include the firstdescriptions and illustrations of the genitalia. Taxonomic notes on all species of the genus and comparisons with related generaare given. A key to all species is provided and geographical distribution data are provided. Morphological evidence is given to support original definition of Trocnadini including only the type genus and a key to tribes of Iassinae is also provided.